Hyperbranched polymer dispersing agent for lithium ion battery positive electrode slurry and preparation method of hyperbranched polymer dispersing agent
By using hyperbranched polymer as a dispersant, its hydrophilicity and branching degree are adjusted, the problem of easy agglomeration of graphene composite materials is solved, the good dispersion effect of graphene is achieved, and the energy density of the battery and the difficulty of the electrode sheet coating process are improved.
Patent Information
- Application Number
- CN202311694653.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-11
- Publication Date
- 2025-06-13
AI Technical Summary
In the prior art, graphene composite materials are prone to agglomeration in application, resulting in a decrease in the volume energy density of the battery and increasing the difficulty of the electrode sheet coating process. The structure and relative molecular mass of the non-ionic polymer dispersant are uncontrollable, resulting in poor anchoring ability of the dispersant and large steric hindrance, resulting in poor dispersion stability of the graphene.
Hyperbranched polymer is used as the dispersant, and its general formula is P(-X-Y)s, block X is an adjustable hydrophilic lipophilic segment, and block Y is an oil-soluble segment. The hydrophilic lipophilicity of the dispersant is adjusted by adjusting the chain length of polyethylene oxide/propylene oxide and the chain length of alkyl phenol/fat alcohol, and the branching degree of the dispersant is adjusted by adjusting the proportion of epoxychlorohydrin, thereby synergistically adjusting the dispersing performance.
Hyperbranched polymer dispersant can effectively reduce liquid viscosity, improve the dispersion stability of particles in the medium, improve the dispersion effect of graphene, reduce the risk of secondary aggregation between the positive electrode slurry particles, increase the cell capacity and reduce AC internal resistance.
Smart Images

Figure CN120137157A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and particularly relates to a hyperbranched polymer dispersant for a positive electrode slurry of a lithium ion battery and a preparation method thereof. Background Art
[0002] With the rapid development and increasing demand of the new energy industry, higher requirements are put forward for lithium ion batteries.
[0003] Currently, the main use of graphene in the field of lithium ion batteries is to utilize the special two-dimensional flexible structure of graphene and its high ionic and electronic conductivity to composite with various active materials to improve their cycle characteristics and high current discharge characteristics. Graphene is a new type of carbon nanomaterial with a specific surface area much larger than that of traditional materials, and its carrier mobility reaches 1.5×10 4 cm 2 / (V·s), which is twice that of indium antimonide material with the highest mobility currently known, and can effectively reduce the migration path of lithium ions and improve the rate performance of the battery. Nanostructuring of materials helps to improve the high-power discharge characteristics of materials, but graphene composites are extremely prone to agglomeration with each other during application, have a low packing density and are difficult to disperse, which will reduce the volume energy density of the battery and increase the difficulty of the electrode coating process.
[0004] Currently, more research has been done on the dispersion problem of active materials, mainly using physical dispersion and chemical dispersion. Physical dispersion is mainly divided into mechanical stirring and ultrasonic dispersion, but it is prone to secondary agglomeration after dispersion, so its application is limited; chemical dispersion mainly includes sodium polyacrylate (PAANa), maleic acid monoglycol monomethyl ether ester and PVP dispersants, etc. These dispersants have been proven to be able to improve the electrochemical performance. To improve the phenomenon that graphene is difficult to disperse and causes graphene agglomeration and sedimentation when compounding with the positive electrode active material, it is necessary to add a small amount of dispersant during the preparation of the positive electrode slurry. Since the dielectric constant of organic solvents is lower than that of water, the ionization ability of ionic dispersants in organic solutions is weak, so non-ionic polymer dispersants can be used in an oil-based environment, and the steric hindrance effect generated after adsorption on the surface of solid particles is used to prevent particle agglomeration.
[0005] The non-ionic polymer dispersants prepared by the prior art are generally comb-shaped, but the structure and relative molecular mass of the comb-shaped dispersants prepared by the prior art are uncontrollable, and the relative molecular mass distribution is wide. Therefore, the anchoring ability of the dispersant is poor and the steric hindrance is large, resulting in poor dispersion stability and unsatisfactory dispersion effect on graphene and other problems.
[0006] Hyperbranched polymers are substances with an irregular, less than 1.0 degree of branching, and approximately ellipsoidal three-dimensional structure. In the same system, hyperbranched polymer dispersants, through anchoring groups and solvation chains, on the one hand, enable functional functional groups (anchoring groups) to be effectively adsorbed on the surface of graphene; on the other hand, induce steric stabilization through the interaction between the solvation chains and the solvent. Therefore, in practical applications, hyperbranched polymer dispersants have characteristics such as effectively reducing the viscosity of liquids, improving the dispersion stability of particles in the medium, and good solubility, which also makes them widely used in fields such as coatings, inks, plastics, optoelectronic materials, nanomaterials, and new energy materials. Summary of the Invention
[0007] To solve the problems existing in the prior art, the present invention provides a hyperbranched polymer dispersant, its preparation method and application, and the hyperbranched polymer dispersant can be used to prepare graphene composite positive electrode slurries.
[0008] To achieve the above object, the technical means adopted by the present invention include:
[0009] A hyperbranched polymer, which uses the hydrophilic core such as the part of polyglycerol and polytrimethylolpropane after removing OH, and the X-Y diblock copolymer as the arm, and its general formula is P(-X-Y)s; wherein, block X is an adjustable hydrophilic-lipophilic chain segment, and block Y is an oil-soluble chain segment; s is an integer greater than 1. For example, s is an integer from 2 to 1000, such as an integer from 10 to 500.
[0010] Further, block X is selected from a polymer chain of one of ethylene oxide and propylene oxide, or a block or random copolymer chain composed of both.
[0011] The oil-soluble chain segment (block Y) is selected from the residues after removing OH from one or more of fatty alcohols and / or alkylphenols.
[0012] According to the embodiments of the present invention, the fatty alcohol is one, two or more of C8-13 fatty alcohols. Preferably, the fatty alcohol is one, two or more of isooctanol, isodecanol, and isotridecanol.
[0013] According to the embodiments of the present invention, the alkylphenol is C6-15 alkylphenol, for example, one, two or more of octylphenol, nonylphenol, and cashew phenol.
[0014] Further, the hyperbranched polymer has the structure shown in formula (I):
[0015]
[0016] Wherein, R 1 、R 2Same or different, and independently selected from each other from the residues after removing the hydroxyl group from C6-15 alkylphenols or C8-13 fatty alcohols; n is an integer from 3 to 15, m is an integer from 1 to 20, and p is an integer from 3 to 15;
[0017] R 3 、R 4 Same or different, and independently selected from each other from H or CH 3 。
[0018] According to an embodiment of the present invention, in the structure shown by formula (I), R 1 、R 2 Same or different, and independently selected from each other from the residues after removing the hydroxyl group from isooctanol, isodecanol, isotridecanol, octylphenol, nonylphenol or cashew phenol; n is an integer from 5 to 10, m is an integer from 5 to 15, and p is an integer from 5 to 10;
[0019] R 3 、R 4 Same or different, and independently selected from each other from H or CH 3 。
[0020] According to an embodiment of the present invention, the weight-average molecular weight of the hyperbranched polymer is between 500 and 30,000, such as 1000 to 20,000, such as 2000 to 10,000.
[0021] According to an embodiment of the present invention, the degree of branching of the hyperbranched polymer is 1 or less, such as 0.8 or less, such as 0.7 or less.
[0022] The present invention also provides a method for preparing the hyperbranched polymer as described above, comprising the following steps:
[0023] (1) An aliphatic alcohol and / or an alkylphenol undergoes a ring-opening polymerization reaction with ethylene oxide and / or propylene oxide to obtain intermediate product 1;
[0024] (2) The intermediate product 1 undergoes a ring-opening polymerization reaction with epichlorohydrin to obtain intermediate product 2;
[0025] (3) An aliphatic alcohol and / or an alkylphenol undergoes a ring-opening polymerization reaction with ethylene oxide and / or propylene oxide to obtain intermediate product 3;
[0026] (4) The intermediate product 2 and the intermediate product 3 undergo a condensation reaction to obtain the hyperbranched polymer.
[0027] According to an embodiment of the present invention, the structure shown by formula (I) is prepared by the following method:
[0028]
[0029]
[0030] Among them, R 1 , R 2 , R 3 , R 4 , m, n, p are defined as described above;
[0031] (S1) Fatty alcohol and / or alkylphenol R 1 OH reacts with ethylene oxide and / or propylene oxide under alkaline conditions to undergo ring-opening polymerization to obtain intermediate 1';
[0032] (S2) The intermediate 1' reacts with epichlorohydrin in the presence of a Lewis acid catalyst to undergo ring-opening polymerization to obtain intermediate 2';
[0033] (S3) Fatty alcohol and / or alkylphenol R 2 OH reacts with ethylene oxide and / or propylene oxide under alkaline conditions to undergo ring-opening polymerization to obtain intermediate 3';
[0034] (S4) The intermediate 2' and the intermediate 3' undergo a condensation reaction under alkaline conditions to obtain the structure shown in formula (I).
[0035] According to an embodiment of the present invention, by mole fraction, in the step (1), 1-5 parts of fatty alcohol and / or alkylphenol R 1 OH, 3-20 parts of ethylene oxide and / or propylene oxide are added; for example, 1-3 parts of fatty alcohol and / or alkylphenol R 1 OH, 5-15 parts of ethylene oxide and / or propylene oxide are added; such as 1-2 parts of fatty alcohol and / or alkylphenol R 1 OH, 8-10 parts of ethylene oxide and / or propylene oxide are added.
[0036] According to an embodiment of the present invention, before performing step (2), the product obtained in step (1) needs to be neutralized to a pH of 5-9, such as 6-8.
[0037] According to an embodiment of the present invention, in the step (2), based on 1-5 molar parts of fatty alcohol and / or alkylphenol R 1 OH in the raw materials of step (1), 3-60 molar parts of epichlorohydrin are added; for example, 5-50 molar parts of epichlorohydrin are added; such as 10-20 molar parts of epichlorohydrin are added.
[0038] According to an embodiment of the present invention, in the step (3), 1-5 molar parts of fatty alcohol and / or alkylphenol R 2OH, add 3 - 20 moles of ethylene oxide and / or propylene oxide; for example, add 1 - 3 moles of fatty alcohol and / or alkylphenol R 2 OH, 5 - 15 moles of ethylene oxide and / or propylene oxide; such as adding 1 - 2 moles of fatty alcohol and / or alkylphenol R 2 OH, 8 - 12 moles of ethylene oxide and / or propylene oxide.
[0039] According to an embodiment of the present invention, in the step (1), in terms of the amount of substance, add an amount of basic catalyst accounting for 0.01 - 0.5% of the amount of fatty alcohol and / or alkylphenol R 1 OH usage, for example, 0.1 - 0.3% of the basic catalyst. The basic catalyst is selected from one or both of potassium hydroxide and sodium hydroxide.
[0040] According to an embodiment of the present invention, in the step (2), in terms of the amount of substance, add an amount of boron trifluoride ether complex BF 1 accounting for 0.3 - 1.5% of the amount of fatty alcohol and / or alkylphenol R 3 ·OC 2 H 5 in step (1), for example, 0.5 - 1% of the boron trifluoride ether complex BF 3 ·OC 2 H 5 .
[0041] According to an embodiment of the present invention, in the step (3), in terms of the amount of substance, add an amount of basic catalyst accounting for 0.01 - 0.5% of the amount of fatty alcohol and / or alkylphenol R 2 OH usage, for example, 0.1 - 0.3% of the basic catalyst. The basic catalyst is selected from one or both of potassium hydroxide and sodium hydroxide.
[0042] According to an embodiment of the present invention, in the step (4), in terms of the amount of substance, add an amount of basic catalyst accounting for 0.01 - 0.5% of the total amount of raw materials in step (4), for example, 0.1 - 0.3% of the basic catalyst. The basic catalyst is selected from one or more of potassium hydroxide and sodium hydroxide.
[0043] According to an embodiment of the present invention, in the step (1), the reaction temperature is 100 - 140 °C, for example, 100 - 120 °C, and the reaction pressure is 0.1 - 0.5 MPa.
[0044] According to an embodiment of the present invention, in the step (2), the reaction temperature is 60 - 90 °C, for example, 60 - 80 °C, and the reaction pressure is 0.1 - 0.5 MPa.
[0045] According to an embodiment of the present invention, in step (3), the reaction temperature is 100 - 140 °C, for example 100 - 120 °C, and the reaction pressure is 0.1 - 0.5 MPa.
[0046] According to an embodiment of the present invention, in step (4), the reaction temperature is 60 - 90 °C, for example 60 - 70 °C, and the reaction pressure is 0.1 - 0.5 MPa.
[0047] The present invention also provides the use of the hyperbranched polymer as described above as a dispersant.
[0048] According to an embodiment of the present invention, the dispersant is used as a dispersant for the positive electrode slurry of a lithium-ion battery, for example, a graphene-modified dispersant for the positive electrode slurry of a lithium-ion battery.
[0049] Beneficial effects
[0050] The hyperbranched polymer provided by the present invention has the following characteristics that other dispersants do not have when used as a dispersant:
[0051] (1) The hydrophilic-lipophilic balance of the dispersant can be adjusted by adjusting the chain lengths of polyethylene oxide / propylene oxide and alkylphenol / fatty alcohol; the degree of branching of the dispersant can be adjusted by adjusting the proportion of epichlorohydrin; the two work together to regulate the dispersion performance of the dispersant. That is, the structure of the dispersant of the present invention can be structurally regulated according to the dispersibility requirements.
[0052] (2) When the raw materials R 1 OH and R 2 OH used to prepare the hyperbranched polymer are isomeric alcohols, such as isodecanol and isotridecanol, the wetting dispersibility and permeability of the dispersant can be further improved, thereby improving the electrode sheet conductivity, first charge specific capacity, first discharge specific capacity, and charge conversion efficiency of the prepared battery.
[0053] (3) The hyperbranched polymer dispersant of the present invention is specifically designed according to the characteristics of the materials contained in the graphene-modified lithium-ion battery positive electrode, and it can be used in the extremely harsh environment of a lithium battery. On the premise of ensuring the conductivity, it reduces the risk of secondary aggregation between the positive electrode slurry particles, improves the fluidity of the positive electrode slurry, reduces the resistance of the electrode sheet, increases the gram capacity of the battery, and reduces the AC internal resistance of the battery. Description of the drawings
[0054] Figure 1 It is a schematic structural diagram of the hyperbranched polymer dispersant of the present invention.
[0055] Figure 2 It is an infrared test diagram of the dispersant prepared in Example 4 of the present invention.
[0056] Figure 31H NMR test chart of the dispersant prepared in Example 4 of the present invention.
[0057] Figure 4 Gel Permeation Chromatography (GPC) test chart of the dispersant prepared in Example 4 of the present invention. Detailed implementation manners
[0058] The embodiments of the present invention will be described in detail below. The following described embodiments are exemplary and are only used to explain the present invention, and should not be construed as a limitation to the present invention.
[0059] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which the present invention belongs. The terms used in the description of the present invention in this specification are only for the purpose of describing specific implementation manners and are not intended to limit the present invention.
[0060] Example 1
[0061] Preparation of hyperbranched polymer dispersant:
[0062] (1) Take the initiator nonylphenol (1 mol), ethylene oxide (5 mol), and the basic catalyst KOH (0.001 mol). The initiator is subjected to a ring-opening polymerization reaction with ethylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 1;
[0063] (2) Neutralize the intermediate product 1 obtained in step (1) with phosphoric acid to pH = 7, and carry out a ring-opening polymerization reaction with epichlorohydrin (8 mol) at 80 °C, 0.1 Mpa, and under the action of the Lewis acid catalyst boron trifluoride ethyl ether complex BF 3 ·OC 2 H 5 (0.005 mol) to obtain intermediate product 2;
[0064] (3) Take the initiator cardanol (1 mol), propylene oxide (6 mol), and the basic catalyst KOH (0.001 mol). The initiator is subjected to a ring-opening polymerization reaction with propylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 3;
[0065] (4) React the intermediate product 2 obtained in step (2) with the intermediate product 3 obtained in step (3) at 60 °C for 2 hours in the presence of the basic catalyst NaOH (0.001 mol) to obtain the hyperbranched polymer dispersant. The structure of the hyperbranched polymer dispersant is as follows, with a theoretical molecular weight M = 6088 and a branching degree DB = 0.65.
[0066]
[0067] Preparation of Graphene Slurry
[0068] Graphene, hyperbranched polymer dispersant, and N-methylpyrrolidone are uniformly mixed to obtain graphene slurry, where graphene accounts for 3 wt% of N-methylpyrrolidone; the dispersant accounts for 0.25 wt% of N-methylpyrrolidone.
[0069] Preparation of Cathode Slurry
[0070] Using N-methylpyrrolidone as a solvent, the dried cathode material lithium iron phosphate, polyvinylidene fluoride (PVDF), and graphene slurry are mixed in a mass ratio of 84:6:10, and coated on aluminum foil to form a pole piece; the obtained pole piece is placed in a vacuum drying oven at 110 °C and dried for 4.5 hours for standby.
[0071] Example 2
[0072] Preparation of Hyperbranched Polymer Dispersant:
[0073] (1) Take the initiator nonylphenol (1 mol), ethylene oxide (10 mol), and basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with ethylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 1;
[0074] (2) Neutralize the intermediate product 1 obtained in step (1) with phosphoric acid to pH = 7, and under the action of Lewis acid catalyst boron trifluoride ether complex BF 3 ·OC 2 H 5 (0.005 mol), react with epichlorohydrin (8 mol) at 80 °C, 0.1 Mpa to obtain intermediate product 2;
[0075] (3) Take the initiator cardanol (1 mol), propylene oxide (12 mol), and basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with propylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 3;
[0076] (4) React the intermediate product 2 obtained in step (2) with the intermediate product 3 obtained in step (3) in the presence of basic catalyst NaOH (0.001 mol) at 60 °C for 2 hours to obtain the hyperbranched polymer dispersant. The structure of the hyperbranched polymer dispersant is as follows, with a theoretical molecular weight M = 9092 and a branching degree DB = 0.65.
[0077]
[0078] Preparation of Graphene Slurry
[0079] Graphene, a hyperbranched polymer dispersant, and N-methylpyrrolidone are uniformly mixed to obtain a graphene slurry, where graphene accounts for 3 wt% of N-methylpyrrolidone; the dispersant accounts for 0.25 wt% of N-methylpyrrolidone.
[0080] Preparation of the positive electrode slurry
[0081] Using N-methylpyrrolidone as a solvent, the dried positive electrode material lithium iron phosphate, polyvinylidene fluoride (PVDF), and the graphene slurry are mixed in a mass ratio of 84:6:10, and coated on an aluminum foil to form a pole piece; the obtained pole piece is placed in a vacuum drying oven at 110 °C and dried for 4.5 hours for standby.
[0082] Example 3
[0083] Preparation of the hyperbranched polymer dispersant:
[0084] (1) Take the initiator nonylphenol (1 mol), ethylene oxide (10 mol), and the basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with ethylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 1;
[0085] (2) Neutralize the intermediate product 1 obtained in step (1) with phosphoric acid until pH = 7, and at 80 °C, 0.1 Mpa, and under the action of the Lewis acid catalyst boron trifluoride ether complex BF 3 ·OC 2 H 5 (0.005 mol), react with epichlorohydrin (8 mol) to undergo a ring-opening polymerization reaction to obtain intermediate product 2;
[0086] (3) Take the initiator isodecyl alcohol (1 mol), propylene oxide (12 mol), and the basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with propylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 3;
[0087] (4) React the intermediate product 2 obtained in step (2) with the intermediate product 3 obtained in step (3) at 60 °C for 2 hours under the action of the basic catalyst NaOH (0.001 mol) to obtain the hyperbranched polymer dispersant. The structure of the hyperbranched polymer dispersant is as follows, its theoretical molecular weight M = 7940, and the degree of branching DB = 0.65.
[0088]
[0089] Preparation of the graphene slurry
[0090] Graphene, a hyperbranched polymer dispersant, and N-methylpyrrolidone are uniformly mixed to obtain a graphene slurry, where graphene accounts for 3 wt% of N-methylpyrrolidone; the dispersant accounts for 0.25 wt% of N-methylpyrrolidone.
[0091] Preparation of the positive electrode slurry
[0092] Using N-methylpyrrolidone as a solvent, the dried positive electrode material lithium iron phosphate, polyvinylidene fluoride (PVDF), and the graphene slurry are mixed in a mass ratio of 84:6:10, and coated on aluminum foil to form a pole piece; the obtained pole piece is placed in a vacuum drying oven at 110 °C and dried for 4.5 hours for standby.
[0093] Example 4
[0094] Preparation of the hyperbranched polymer dispersant:
[0095] (1) Take the initiator isomeric tridecanol (1 mol), ethylene oxide (10 mol), and the basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with ethylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 1;
[0096] (2) Neutralize the intermediate product 1 obtained in step (1) with phosphoric acid to pH = 7, and under the action of boron trifluoride ether complex BF 3 ·OC 2 H 5 (0.005 mol) and epichlorohydrin (8 mol) to undergo a ring-opening polymerization reaction to obtain intermediate product 2;
[0097] (3) Take the initiator isomeric decanol (1 mol), propylene oxide (12 mol), and the basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with propylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 3;
[0098] (4) React the intermediate product 2 obtained in step (2) with the intermediate product 3 obtained in step (3) in the presence of the basic catalyst NaOH (0.001 mol) at 60 °C for 2 hours to obtain the hyperbranched polymer dispersant. The structure of the hyperbranched polymer dispersant is as follows, its theoretical molecular weight M = 7920, and the degree of branching DB = 0.65.
[0099]
[0100] Preparation of the graphene slurry
[0101] Graphene, a hyperbranched polymer dispersant, and N-methylpyrrolidone are uniformly mixed to obtain a graphene slurry, where graphene accounts for 3 wt% of N-methylpyrrolidone; the dispersant accounts for 0.25 wt% of N-methylpyrrolidone.
[0102] Preparation of the positive electrode slurry
[0103] Using N-methylpyrrolidone as a solvent, the dried positive electrode material lithium iron phosphate, polyvinylidene fluoride (PVDF), and the graphene slurry are mixed in a mass ratio of 84:6:10, and coated on an aluminum foil to form a pole piece; the obtained pole piece is placed in a vacuum drying oven at 110 °C and dried for 4.5 hours for standby.
[0104] Example 5
[0105] Preparation of the hyperbranched polymer dispersant:
[0106] (1) Take the initiator nonylphenol (1 mol), ethylene oxide (5 mol), and the basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with ethylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 1;
[0107] (2) Neutralize the intermediate product 1 obtained in step (1) with phosphoric acid to pH = 7, and at 80 °C, 0.1 Mpa, and under the action of the Lewis acid catalyst boron trifluoride ethyl ether complex BF 3 ·OC 2 H 5 (0.005 mol), react with epichlorohydrin (15 mol) to undergo a ring-opening polymerization reaction to obtain intermediate product 2;
[0108] (3) Take the initiator cardanol (1 mol), propylene oxide (6 mol), and the basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with propylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 3;
[0109] (4) React the intermediate product 2 obtained in step (2) with the intermediate product 3 obtained in step (3) at 60 °C for 2 hours under the action of the basic catalyst NaOH (0.001 mol) to obtain the hyperbranched polymer dispersant. The structure of the hyperbranched polymer dispersant is as follows, its theoretical molecular weight M = 11030, and the degree of branching DB = 0.66.
[0110]
[0111] Preparation of the graphene slurry
[0112] Graphene, hyperbranched polymer dispersant, and N-methylpyrrolidone are uniformly mixed to obtain a graphene slurry, where graphene accounts for 3 wt% of N-methylpyrrolidone; the dispersant accounts for 0.25 wt% of N-methylpyrrolidone.
[0113] Preparation of the positive electrode slurry
[0114] Using N-methylpyrrolidone as a solvent, the dried positive electrode material lithium iron phosphate, polyvinylidene fluoride (PVDF), and the graphene slurry are mixed in a mass ratio of 84:6:10, and coated on an aluminum foil to form a pole piece; the obtained pole piece is placed in a vacuum drying oven at 110 °C and dried for 4.5 hours for standby.
[0115] Example 6
[0116] Preparation of the hyperbranched polymer dispersant:
[0117] (1) Take the initiator nonylphenol (1 mol), propylene oxide (5 mol), and the basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with propylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 1;
[0118] (2) Neutralize the intermediate product 1 obtained in step (1) with phosphoric acid to pH = 7, and at 80 °C, 0.1 Mpa, and under the action of the Lewis acid catalyst boron trifluoride ether complex BF 3 ·OC 2 H 5 (0.005 mol) reacts with epichlorohydrin (5 mol) to undergo a ring-opening polymerization reaction to obtain intermediate product 2;
[0119] (3) Take the initiator nonylphenol (1 mol), propylene oxide (5 mol), and the basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with propylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 3;
[0120] (4) React the intermediate product 2 obtained in step (2) with the intermediate product 3 obtained in step (3) in the presence of the basic catalyst NaOH (0.001 mol) at 60 °C for 2 hours to obtain the hyperbranched polymer dispersant. The structure of the hyperbranched polymer dispersant is as follows, with a theoretical molecular weight M = 3340 and a branching degree DB = 0.65.
[0121]
[0122] Preparation of the graphene slurry
[0123] Graphene, hyperbranched polymer dispersant, and N-methylpyrrolidone are uniformly mixed to obtain a graphene slurry, where graphene accounts for 3 wt% of N-methylpyrrolidone; the dispersant accounts for 0.25 wt% of N-methylpyrrolidone.
[0124] Preparation of the positive electrode slurry
[0125] Using N-methylpyrrolidone as a solvent, the dried positive electrode material lithium iron phosphate, polyvinylidene fluoride (PVDF), and the graphene slurry are mixed in a mass ratio of 84:6:10, and coated on aluminum foil to form a pole piece; the obtained pole piece is placed in a vacuum drying oven at 110 °C and dried for 4.5 hours for standby.
[0126] Example 7
[0127] Preparation of the hyperbranched polymer dispersant:
[0128] (1) Take the initiator cardanol (1 mol), propylene oxide (5 mol), and the basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with propylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 1;
[0129] (2) Neutralize the intermediate product 1 obtained in step (1) with phosphoric acid until pH = 7. At 80 °C, 0.1 Mpa, and under the action of the Lewis acid catalyst boron trifluoride ether complex BF 3 ·OC 2 H 5 (0.005 mol), react with epichlorohydrin (5 mol) to undergo a ring-opening polymerization reaction to obtain intermediate product 2;
[0130] (3) Take the initiator cardanol (1 mol), propylene oxide (5 mol), and the basic catalyst KOH (0.001 mol). The initiator undergoes a ring-opening polymerization reaction with propylene oxide at 120 °C, 0.5 Mpa, and under the action of the basic catalyst KOH to obtain intermediate product 3;
[0131] (4) React the intermediate product 2 obtained in step (2) with the intermediate product 3 obtained in step (3) in the presence of the basic catalyst NaOH (0.001 mol) at 60 °C for 2 hours to obtain the hyperbranched polymer dispersant. The structure of the hyperbranched polymer dispersant is as follows, with a theoretical molecular weight M = 3832 and a branching degree DB = 0.65.
[0132]
[0133] Preparation of the graphene slurry
[0134] Graphene, a hyperbranched polymer dispersant, and N-methylpyrrolidone are uniformly mixed to obtain a graphene slurry, where graphene accounts for 3 wt% of N-methylpyrrolidone; the dispersant accounts for 0.25 wt% of N-methylpyrrolidone.
[0135] Preparation of the positive electrode slurry
[0136] Using N-methylpyrrolidone as a solvent, the dried positive electrode material lithium iron phosphate, polyvinylidene fluoride (PVDF), and the graphene slurry are mixed in a mass ratio of 84:6:10, and coated on an aluminum foil to form a pole piece; the obtained pole piece is placed in a vacuum drying oven at 110 °C and dried for 4.5 hours for standby.
[0137] Comparative Example 1
[0138] Preparation of the graphene slurry
[0139] Graphene and N-methylpyrrolidone are uniformly mixed to obtain a graphene slurry, where graphene accounts for 3 wt% of the solvent.
[0140] Preparation of the positive electrode slurry
[0141] Using N-methylpyrrolidone as a solvent, the dried positive electrode material lithium iron phosphate, polyvinylidene fluoride (PVDF), and the graphene slurry are mixed in a mass ratio of 84:6:10, and coated on an aluminum foil to form a pole piece; the obtained pole piece is placed in a vacuum drying oven at 110 °C and dried for 4.5 hours for standby.
[0142] Comparative Example 2
[0143] The linear polymer dispersant is nonylphenol polyoxyethylene ether (NP-50), supplier: Jiangsu Haian Petrochemical Factory, and its structure is as follows, with a theoretical molecular weight M = 2420.
[0144]
[0145] Preparation of the graphene slurry
[0146] Graphene, nonylphenol polyoxyethylene ether (NP-50), and N-methylpyrrolidone are uniformly mixed to obtain a graphene slurry, where graphene accounts for 3 wt% of N-methylpyrrolidone; nonylphenol polyoxyethylene ether (NP-50) accounts for 0.25 wt% of N-methylpyrrolidone.
[0147] Preparation of the positive electrode slurry
[0148] Using N-methylpyrrolidone as a solvent, the dried positive electrode material lithium iron phosphate, polyvinylidene fluoride (PVDF), and the graphene slurry are mixed in a mass ratio of 84:6:10, and coated on an aluminum foil to form a pole piece; the obtained pole piece is placed in a vacuum drying oven at 110 °C and dried for 4.5 hours for standby.
[0149] The graphene slurries obtained in Comparative Examples 1-2 and Examples 1-7 were allowed to stand for 24 h and one week, and their changes were observed. Subsequently, 5 ml of the graphene slurries in Comparative Examples 1-2 and Examples 1-7 were taken respectively, centrifuged at 5000 r / min for 10 min, and the state of the slurry after centrifugation was observed. The results are shown in Table 1.
[0150] Table 1 Observation results of 24 h and one-week standing / centrifugation of Comparative Examples 1-2 and Examples 1-7
[0151]
[0152]
[0153] As can be seen from Table 1, after standing for 24 h and one week, in Comparative Example 1 without a dispersant and Comparative Example 2 with a linear polymer dispersant, it was observed that the slurry was almost completely stratified, the supernatant was almost transparent, and there was a large amount of precipitation at the bottom of the bottle. When the graphene slurries of Comparative Examples 1-2 and Examples 1-7 were centrifuged, it was found that all the graphene in Comparative Examples 1-2 was deposited at the bottom of the centrifuge tube, while the graphene slurries of Examples 1-7 had almost no deposition and were all dispersed in the solution. The results in Examples 1-7 show that the hyperbranched polymer dispersant has a good exfoliation effect on graphene and effectively prevents the accumulation of graphene, thus achieving the effect of being dispersed in the solution.
[0154] The freshly prepared slurries were directly tested respectively, and the slurries after standing for 24 hours were stirred for 1 min and then tested. A Lichen ND-10 rotary viscometer was used, with a 2# rotor. The rotor was inserted into the slurry to be tested, the test rotation speed was 60 rpm, and the time was 1 minute. The average value was taken at multiple points to obtain the slurry viscosity value. The test results are shown in Table 2.
[0155] Table 2 Viscosity and solid content of the slurries of Comparative Examples 1-2 and Examples 1-7 after the graphene dispersion was made into the positive electrode slurry
[0156]
[0157]
[0158] As can be seen from the data in Table 2, after 24 h, Comparative Examples 1-2 had become gels, while the slurries of Examples 1-7 were still fluid.
[0159] Performance evaluation:
[0160] The obtained aligned lithium-ion battery positive electrode materials coated with graphene in each example were made into button cells, and the following performance tests were carried out.
[0161] The preparation method of the button battery is as follows: The electrode sheet is roll-pressed on a rolling machine, and the roll-pressed electrode sheet is punched into circular electrode sheets of appropriate size. The battery assembly is carried out in a glove box filled with argon. The electrolyte of the electrolyte is 1M LiPF6, the solvent is EC:DEC:DMC = 1:1:1 (volume ratio), and the lithium metal sheet is the counter electrode. The conductivity of the positive electrode sheet is measured by a four-probe tester RTS-9, and the electrochemical performance is carried out on an Ivium-n-stat electrochemical workstation.
[0162] Table 3 Electrochemical performance of Comparative Examples 1-2 and Examples 1-7
[0163]
[0164] It can be seen from the data in Table 3 that, compared with Comparative Examples 1-2, the primary conductivity of the electrode sheets prepared in Examples 1-7 with the addition of hyperbranched polymer dispersants has been greatly improved. This is because no dispersant was added in Comparative Example 1, resulting in the aggregation of graphene in the positive electrode slurry, forming larger aggregates, the poor fluidity of the positive electrode slurry, which is not conducive to coating, and at the same time resulting in a decrease in the conductivity between the active positive electrode materials and a decrease in the electron transport ability. In Comparative Example 2, the added linear polymer dispersant has poor dispersion effect, and graphene aggregates quickly in the system. Moreover, the charge conversion efficiency of the electrode sheets prepared in Examples 1-7 is significantly higher than that of Comparative Examples 1 and 2, proving that graphene is well dispersed in the positive electrode slurry, and the dispersant has no adverse effect on the electrochemical performance of the positive electrode slurry. Compared with other examples, the electrode sheets of Examples 3 and 4 have higher conductivity, first charge specific capacity, first discharge specific capacity and charge conversion efficiency, because the dispersant structure uses isomeric alcohol as the initiator, and the prepared dispersant makes graphene disperse better in the positive electrode slurry.
[0165] As mentioned above, the embodiments of the present invention have been described. However, the present invention is not limited to the above embodiments. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A hyperbranched polymer, characterized in that it is a polymer with the hydrophilic core being the part after removing OH from polyglycerol and polytrimethylolpropane, and the arms being X-Y diblock copolymers, and its general formula is P(-X-Y)s; wherein, block X is an adjustable hydrophilic-lipophilic chain segment, and block Y is an oil-soluble chain segment; s is an integer greater than 1.
2. The hyperbranched polymer according to claim 1, characterized in that the block X is selected from a polymer chain of one of ethylene oxide and propylene oxide, or a block or random copolymer chain composed of both; Preferably, the oil-soluble chain segment is selected from the residues after removing OH from one or more of fatty alcohols and / or alkylphenols; Preferably, the fatty alcohol is one, two or more of C8-13 fatty alcohols; Preferably, the alkylphenol is one, two or more of C6-15 alkylphenols.
3. The hyperbranched polymer according to claim 1 or 2, characterized in that the hyperbranched polymer has the structure shown in formula (I): wherein, R 1 , R 2 are the same or different and are each independently selected from the residue obtained by removing the hydroxyl group from a C6-15 alkylphenol or a C8-13 fatty alcohol; n is an integer from 3 to 15, m is an integer from 1 to 20, and p is an integer from 3 to 15; R 3 、R 4 are the same or different and are each independently selected from H or CH 3 .
4. The hyperbranched polymer according to claim 3, characterized in that In the structure represented by formula (I), R 1 , R 2 are the same or different and each independently selected from the residues obtained by removing the hydroxyl group from isooctanol, isodecanol, isotridecanol, octylphenol, nonylphenol or cardanol; n is an integer from 5 to 10, m is an integer from 5 to 15, and p is an integer from 5 to 10; R 3 、R 4 are the same or different and are each independently selected from H or CH 3 .
5. The hyperbranched polymer according to claim 3 or 4, characterized in that the weight-average molecular weight of the hyperbranched polymer is between 500 and 30,000; Preferably, the degree of branching of the hyperbranched polymer is below 1.
6. The preparation method of the hyperbranched polymer according to any one of claims 1-5, characterized in that it includes the following steps: (1) Fatty alcohols and / or alkylphenols react with ethylene oxide and / or propylene oxide by ring-opening polymerization to obtain intermediate product 1; (2) The intermediate product 1 reacts with epichlorohydrin by ring-opening polymerization to obtain intermediate product 2; (3) Fatty alcohols and / or alkylphenols react with ethylene oxide and / or propylene oxide by ring-opening polymerization to obtain intermediate product 3; (4) The intermediate product 2 and the intermediate product 3 undergo a condensation reaction to obtain the hyperbranched polymer.
7. The preparation method according to claim 6, characterized in that the structure shown in formula (I) is prepared by the following method: wherein, R 1 , R 2 , R 3 , R 4 , m, n, p have the definitions described in claim 3 or 4; (S1) Fatty alcohol and / or alkylphenol R 1 OH and ethylene oxide and / or propylene oxide Under alkaline conditions, a ring-opening polymerization reaction occurs to obtain intermediate product 1'; (S2) The intermediate product 1' reacts with epichlorohydrin by ring-opening polymerization in the presence of a Lewis acid catalyst to obtain intermediate product 2'; (S3) Fatty alcohol and / or alkylphenol R 2 OH and ethylene oxide and / or propylene oxide undergo ring-opening polymerization reaction under alkaline conditions to obtain intermediate 3'; (S4) The intermediate product 2' and the intermediate product 3' undergo a condensation reaction under alkaline conditions to obtain the structure shown in formula (I).
8. The preparation method according to claim 7, characterized in that In terms of molar parts, in the step (1), 1-5 parts of fatty alcohol and / or alkylphenol R 1 OH, 3-20 parts of ethylene oxide and / or propylene oxide are added; Preferably, in the step (2), 3 - 60 parts of epichlorohydrin are added based on 1 - 5 moles of fatty alcohol and / or alkylphenol R 1 in terms of OH; Preferably, in the step (3), 1-5 molar parts of fatty alcohol and / or alkylphenol R 2 OH is added, and 3-20 parts of ethylene oxide and / or propylene oxide are added; Preferably, in the step (1), a basic catalyst is added in an amount of 0.01-0.5% based on the amount of the fatty alcohol and / or alkylphenol R 1 OH by molar amount; Preferably, the alkaline catalyst is selected from one or both of potassium hydroxide and sodium hydroxide; Preferably, in the step (2), boron trifluoride ether complex BF 1 is added in an amount of 0.3-1.5% of the amount of the fatty alcohol and / or alkylphenol R 3 ·OC 2 H 5 used in the step (1) in terms of the amount of substance; Preferably, in the step (3), a basic catalyst is added in an amount of 0.01-0.5% based on the amount of the fatty alcohol and / or alkylphenol R 2 OH used in terms of the amount of substance; Preferably, the alkaline catalyst is selected from one or both of potassium hydroxide and sodium hydroxide. Preferably, in the step (4), a basic catalyst is added in an amount of 0.01-0.5% by mole of the total amount of the raw materials in the step (4); Preferably, in the step (1), the reaction temperature is 100-140 °C and the reaction pressure is 0.1-0.5 MPa; Preferably, in the step (2), the reaction temperature is 60-90 °C and the reaction pressure is 0.1-0.5 MPa; Preferably, in the step (3), the reaction temperature is 100 - 140 °C, and the reaction pressure is 0.1 - 0.5 MPa; Preferably, in the step (4), the reaction temperature is 60 - 90 °C, and the reaction pressure is 0.1 - 0.5 MPa.
9. Use of the hyperbranched polymer according to any one of claims 1 - 5 as a dispersant.
10. According to the use described in claim 9, characterized in that the dispersant is used as a dispersant for the positive electrode slurry of a lithium - ion battery.